USE OF AGROINDUSTRIAL BY-PRODUCTS IN THE PRODUCTION OF BRIQUETTES - Zanovelli Nalevaiko, Jaqueline; André Cremonez, Paulo; Gustavo Teleken, Joel (Revista Brasileira de Engenharia de Biossistemas, 2021)
The current world energy scenario is the search for cleaner fuels and new sources of renewable energy, with emphasis on the use of residual biomass. The present work seeks to evaluate the physical-chemical characteristics of briquettes produced from sugarcane bagasse, cassava bagasse and poultry litter.The by-products underwentanalysis before and after briquetting. Briquettes with different mixture percentages (M1, M2 and M3) were produced. The briquettes produced presented values of energetic efficiency, mechanical resistance and apparent and energetic density consistent with values in the literature and international standards. Regarding the ash content, none of them fit in the European briquettes manufacturing parameters. The mixture with better energy efficiency was M2, with a calorific value of 16.41 MJ/kg and also the smallest ash content of 7.96% and the best C/H ratio, hydrogen and carbon percentage, thus being the one with the largest burning energy potential. The use of briquettes produced from residual biomass presents many advantages, contributing to economic, social and environmental aspects.